Law Enforcement of Illegal Logging in Indonesia: Problems and Challenges in Present and the Future - Dekiawati, Erla Sari (Indonesian Journal of Environmental Law and Sustainable Development, 2022)
Implementation of environmental protection in juridical forest area has been regulated in Law No. 18 of 2013, on the prevention and eradication of forest destruction. In fact, the implementation of laws on the prevention and eradication of forest destruction is still at issue. Problems about efficiency and effectiveness of enforcement provided by the government. Through the methodology, it can answer the understanding of society and philosophical basis of legislation on the prevention and eradication of forest destruction and can improve the quality of enforcement of the law as well as the role given by the government. This study is expected to provide evaluation and enhancement of law enforcement in forest area protection.